The Factors That Influence The Purchasing Decisions Local Cosmetic Products - Anisah Anisah; Nurul Khotimah; Maria Y Aryati (Ilomata International Journal of Management, 2022)
The purpose of this study was to analyze the effects of celebrity endorsers, brand image, brand trust, and lifestyle on purchasing decisions of local cosmetic products. The method used in this study uses primary data with a sample of 178 respondents, both users and those who have used local cosmetic products. Data collection techniques use non-probability sampling. The data used in this study uses validity tests, reliability tests, classical assumption tests, T tests, F tests, multiple linear analysis, and coefficient of determination. The findings revealed that celebrity endorsement, brand trust, and lifestyle influence the purchase of local cosmetic products, whereas brand image has no effect. Celebrity endorsers, brand image, brand trust, lifestyle and price simultaneously influence the decisions of local cosmetic product buyers.